Hexagonal phase with ordered acyl chains formed by a short chain asymmetric ceramide - Dupuy, Fernando Gabriel (2017)
Ceramides constitute a group of lipids with usually high melting temperature that also favor negative curvature in membranes when mixed with other lipids. The short chain C10:0 ceramide is an asymmetric lipid which consists of an 18 carbon sphingosine base N-acylated with decanoic acid. According to high sensitivity differential scanning calorimetry, it shows a minor exothermic peak at 61 °C and a main endothermic transition at 75 °C. By small angle X-ray scattering and polarized light microscopy we found that, at temperatures below the main transition, the fully hydrated lipid dispersions are arranged in a tridimensional structure corresponding to an inverted hexagonal phase. Infrared spectroscopy and wide angle X-ray diffraction indicated that the acyl chains of ceramides exhibit a relatively high order in the hexagonal phase. As far as we know, this is the first report of a lipid hexagonal phase having highly ordered acyl chains. Molecular asymmetry due to the different length of the sphingosine and the N-acyl chains of C10:0 ceramide may explain why this novel phase is formed.